Preferences for green infrastructure and green stormwater infrastructure in urban landscapes: Differences between designers and laypeople - Pongsakorn Suppakittpaisarn (2019)
© 2019 Many cities in the US have implemented Green Stormwater Infrastructure (GSI) to manage stormwater. Because several types of GSI are relatively new, we do not know how people perceive GSI or the extent to which they prefer various configurations of GSI. We also do not know the extent to which laypeople perceive GSI differently from designers. This lack of knowledge costs us: we risk creating GSI that people find unappealing, and if they do not like it, they may not want to spend time in or near it, they may not maintain it, and they may not reap health benefits from it. In this study, 497 laypeople and 117 designers provided preference ratings of 55 photographs of GSI. We used factor analysis to identify the categories of GSI that people perceive. We found that landscapes with any GSI are significantly more preferred than landscapes with no GSI, and that the messiness of GSI impacted preference. Designers’ preferences were similar to those of laypeople, except that designers had a greater dislike for images consisting of lawns and retention ponds compared to laypeople, and designers had a slightly greater preference for newer forms of GSI, such as green roofs and bio-retentions. Designers can use these results to create preferred landscapes that manage stormwater while promoting the wellbeing of the people they serve.